Penerapan Model Pembelajaran Kooperatif Tipe STAD Dalam Meningkatkan Aktivitas dan Hasil Belajar Pada Mata Kuliah Konsep Dasar Matematika - Yunita Wildaniati (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
STAD model begins with the presentation of learning materials, grouping students into groups, guiding study groups, evaluating learning outcomes, and rewarding. Type of research used in this research is Classroom Action Research. The conclusions of this study are: STAD can increase student learning activity, this is seen from the average percentage of student learning activities from cycle I to cycle II increased 22.65% to 85.45%. The percentage of students who finished studying in cycle I to cycle II increased 60% to 90%. This is reinforced by t test and based on post test result of cycle I and cycle II is obtained to: 5,86 while at 1% significance ttable obtained equal to 3,25. Because to> tt; this means that the difference of score of learning outcomes in students between before and after applied method is a significant difference.